Interfaith Marriage in the Perspectives of Indonesian Tafsir Ulama: Reviewing the Tafsir of Hamka, Quraish Shihab, and Musdah Mulia - Mutaqin, Ayi Zaenal; Yunus, Badruzzaman M.; Qomaruzzaman, Bambang (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2022)
The discourse on interfaith marriage is still a topic that is always discussed by Islamic thinkers today, along with the large number of Muslims in Indonesia who practice it. This paper will examine the tafsir of interfaith marriages from the perspective of Indonesian scholars of tafsir, namely Hamka, Quraish Shihab, and Musdah Mulia, including the socio-political driving factors of these scholars conclude the tafsir of interfaith marriages. This research is qualitative research using library data sources. The study results indicate differences in tafsir by these three commentators, where Hamka and Quraish Shihab generally conclude that interfaith marriages are prohibited. However, both of them also allow men to marry Ahli Kitab (Jews and Christians) on the grounds of an emergency or for the sake of Islamic da'wah. On the other hand, Musdah Mulia allowed interfaith marriages because there were no clear arguments for interfaith marriages. Musdah Mulia also reasoned that there is no concrete evidence that interfaith marriage is the cause of the breakdown of a family, where interfaith marriages also help keep family life in harmony. This difference in conclusions was driven by socio-political factors when the three ulama worked, especially in adjusting to the context of national political stability.